Explanation in historical linguistics - Davis, Garry W.; Iverson, Gregory K. (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 1992)
This is the first of two volumes deriving from papers presented at the Nineteenth Annual UVM Linguistics Symposium held in Milwaukee in April 1990. The contributions in this volume investigate the general question of what constitutes an explanation of diachronic change, and illustrate their proposals in the context of various specific problems in historical linguistics. The present volume also includes a solicited paper by Eric P. Hamp ("On remote reconstruction") that addresses the validity of distant reconstructions like those of Nostratic and Proto-World. Content: Garry W. Davis & Gregor